From Tradition to Court: The Legal Validity of the Sumpah Pocong in Civil Evidence - Setiawan, Tiffany; Kurniawan, Jackline; Kandou, Annabella; Asriyani, Arini; Al-Maliki, Abbas Ibrahim (Amsir Law Journal, 2026)
Civil procedural law places oath evidence as the final evidentiary instrument (ultimum remedium) when documentary evidence, witness testimony, presumptions, and confessions are no longer sufficient to convince the judge. Building on the strategic position of oaths in the evidentiary system, this article examines the validity of the sumpah pocong as a form of oath-taking in civil cases, with a focus on its normative, juridical‑practical, and sociological dimensions. This study employs a normative juridical method with statutory, conceptual, and case approaches to the regulation of oaths in the Civil Code, the HIR/RBg, the Law on Judicial Power, and the decision of the Religious Court of Lumajang No. 1252/Pdt.G/1996/PA.Lmj, combined with a review of literature and doctrine on civil evidence and the practice of the sumpah pocong. The findings show, first, that oaths in civil procedural law occupy a special position as evidence with litis decissoir force in the form of a decisive oath, while at the same time carrying a strong moral‑religious burden in encouraging the parties’ honesty. Second, the sumpah pocong is not recognized as a separate category of evidence, but can functionally be accepted as the implementation of a decisive oath insofar as it is ordered by the judge, used as a last resort when proof has reached an impasse, carried out in accordance with the religion of the party taking the oath, and officially documented in the minutes of the hearing. Third, the practice of accepting the sumpah pocong indicates an effort by the judiciary to accommodate legal values and the sense of justice living in society, while at the same time giving rise to problems of legal certainty and consistency of application due to the absence of explicit regulation. This article concludes that the position of the sumpah pocong in civil procedural law is casuistic and based on functional legality, so that clearer normative guidelines are needed in the future to ensure that the integration between religious/customary practices and the civil evidentiary system remains in line with the principles of legality and the rule of law.